2021
DOI: 10.1084/jem.20210250
|View full text |Cite
|
Sign up to set email alerts
|

The RAG1 N-terminal region regulates the efficiency and pathways of synapsis for V(D)J recombination

Abstract: Immunoglobulin and T cell receptor gene assembly depends on V(D)J recombination initiated by the RAG1-RAG2 recombinase. The RAG1 N-terminal region (NTR; aa 1–383) has been implicated in regulatory functions whose influence on V(D)J recombination and lymphocyte development in vivo is poorly understood. We generated mice in which RAG1 lacks ubiquitin ligase activity (P326G), the major site of autoubiquitination (K233R), or its first 215 residues (Δ215). While few abnormalities were detected in R1.K233R mice, R1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…We find that loss of RAG1 E3 ligase activity within the NTR does not alter NF‐κB2 activation, expression of Cd40 and Pim2 transcripts, or induction of PIM2 protein. Consistent with our results, Beilinson et al (2021) also demonstrated that RAG1 ubiquitin ligase activity did not regulate Pim2 transcripts or protein in primary pre‐B cells. Thus, RAG1 directs ncDDR in pre‐B cells through both non‐core region‐dependent and ‐independent activities that do not depend on its E3 ligase.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We find that loss of RAG1 E3 ligase activity within the NTR does not alter NF‐κB2 activation, expression of Cd40 and Pim2 transcripts, or induction of PIM2 protein. Consistent with our results, Beilinson et al (2021) also demonstrated that RAG1 ubiquitin ligase activity did not regulate Pim2 transcripts or protein in primary pre‐B cells. Thus, RAG1 directs ncDDR in pre‐B cells through both non‐core region‐dependent and ‐independent activities that do not depend on its E3 ligase.…”
Section: Resultssupporting
confidence: 93%
“…The importance of these non‐core regions of RAG1 in lymphocyte development is underscored by the identification of mutations in these domains in patients with primary immune deficiency (Lee et al , 2014; Notarangelo et al , 2016). Further, mice expressing only core RAG1 exhibit aberrant V(D)J recombination, abnormal lymphocyte development, and increased incidence of malignancies, suggesting a key role of these regions in RAG function and immune development (Talukder et al , 2004; Deriano et al , 2011; Horowitz & Bassing, 2014; Beilinson et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Overlapping with this domain is a RING motif, at residues 264-389, which has the capability to act as an E3 ubiquitin ligase for both autoubiquitylation and modification of other proteins (Grazini et al, 2010). RAG1 autoubiquitylation at K233 has been shown to stimulate cleavage activity in a cell free assay and exhibit post-transcriptional regulation in mice studies (Singh and Gellert, 2015;Beilinson et al, 2021). Ubiquitin modification of other proteins occurs at different stages of recombination, such as polyubiquitylation of KPNA1 or the monoubiquitylation of histones (discussed below).…”
Section: Rag1 Non-core Domain Functionmentioning
confidence: 99%
“…RAG1 has the DNA binding and cleaving activity to cut the heptamer of RSSs to generate blunt RSS ends and hairpin-associated coding ends ( Figures 2B–D ) ( McBlane et al, 1995 ; van Gent et al, 1995 ; Alt et al, 2013 ). RAG1 interacts with numerous nucleolar proteins to modulate recombination activity in the nucleus ( Brecht et al, 2020 ), and the N-terminal region of RAG1 regulates the efficiency and pathways of synapsis for V(D)J recombination ( Beilinson et al, 2021 ). RAG2 has no DNA cleavage activity, but it is required to enhance RAG1 catalytic activity.…”
Section: V(d)j Recombinationmentioning
confidence: 99%